Blockade of myeloid differentiation 2 attenuates diabetic nephropathy by reducing activation of the renin‐angiotensin system in mouse kidneys. (23rd May 2019) - Wang, Yi; Fang, Qilu; Jin, Yiyi; Liu, Zhoudi; Zou, Chunpeng; Yu, Weihui; Li, Weixin; Shan, Xiaoou; Chen, Ruijie; Khan, Zia; Liang, Guang
Abstract : Background and Purpose: Both innate immunity and the renin‐angiotensin system (RAS) play important roles in the pathogenesis of diabetic nephropathy (DN). Myeloid differentiation factor 2 (MD2) is a co‐receptor of toll‐like receptor 4 (TLR4) in innate immunity. While TLR4 is involved in the development of DN, the role of MD2 in DN has not been characterized. It also remains unclear whether the MD2/TLR4 signalling pathway is associated with RAS activation in diabetes. Experimental Approach: MD2 was blocked using siRNA or the low MW inhibitor, L6H9, in renal proximal tubular cells (NRK‐52E cells) exposed to high concentrations of glucose (HG). In vivo, C57BL/6 and MD2 −/− mice were injected with streptozotocin to induce Type 1 diabetes and nephropathy. Key Results: Inhibition of MD2 by genetic knockdown or the inhibitor L6H9 suppressed HG‐induced expression of ACE and angiotensin receptors and production of angiotensin II in NRK‐52E cells, along with decreased fibrosis markers (TGF‐β and collagen IV). Inhibition of the MD2/TLR4‐MAPKs pathway did not affect HG‐induced renin overproduction. In vivo, using the streptozotocin‐induced diabetic mice, MD2 was overexpressed in diabetic kidney. MD2 gene knockout or L6H9 attenuated renal fibrosis and dysfunction by suppressing local RAS activation and inflammation. Conclusions and Implications: Hyperglycaemia activated the MD2/TLR4‐MAPKs signalling cascade to induce renal RAS activation, leading to renal fibrosis and dysfunction. Pharmacological inhibition of MD2 may be considered as a therapeutic approach to mitigate DN and the low MW inhibitor L6H9 could be a candidate for such therapy.